Analisis Implementasi Penerapan SAK ETAP Pada Laporan Keuangan BUM Desa Tridaya Mandiri Desa Bhuana Jaya Kecamatan Tenggarong Seberang Kabupaten Kutai Kartanegara - E Y Suharyono 3, Siti Maesaroh1, Imam Nazarudin Latif2 (EKONOMIA, 2021)
ABSTRACTThe purpose of this study is to find out and present the suitability of BUM Desa Tridaya Mandiri Bhuana Jaya Village, Tenggarong Seberang District, Kutai Kartanegara regencie and SAK ETAP (2019:1).The basic theory used is the theory of financial accounting using descriptive qualitative analysis tools, namely the application of SAK ETAP in the preparation and presentation of BUM Tridaya Mandiri financial statements. Lost and profit reports, equity change reports,Cash flow reports.Type of descriptive qualitative research. The qualitative descriptive method was chosen because the research conducted was related to the ongoing events.Based on the results of the analysis and discussion it is known that in its financial reporting, BUM Desa Tridaya Mandiri does not present reports on changes in equity, cash flow statements, and also notes to financial statements. Accounting practices in BUM Desa refer to SAK ETAP (2019) have not been implemented due to limited accounting knowledge among BUM Desa managers so they do not practice adequate accounting processes. Not optimal implementation of accounting practices and the use of accounting information in BUM Desa so far is not solely a mistake or lack of BUM Desa managers, but also due to the suboptimal participation of the government and universities in encouraging and facilitating accounting practices in BUM Desa.